Analisis Kebutuhan Modal Kerja PT Kersa Gunung Wasada pada Tahun 2017 di samarinda - jumiati jumiati (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
ABSTRACTJumiati. Analysis of Working Capital Requirements in PT Kersa Gunung Wasada in 2017 at Samarinda. Under guidance by Mr Irwansyah as first supervisor and Mr Ibnu Abni Lahaya as second supervisor.         Formulation of the problem in this research is “ what is working capital available and needed to guarantee the operational activities the year 2017 in PT Kersa Gunung Wasada at Samarinda.The purpose of this research is to find out and analyze the magnitude of working capital needs and the availability of working capital in support of operational activities on PT Kersa Gunung Wasada in the year 2017 at samarinda. The benefit of this research are as consideration for corporate leaders, especially in determining the magnitude of carefully working capital and can serve as knowledge for leadership of the company in future decisions will be come.Analitycal tools used in this writing is a method of rotation of the elements of working capital and the method of least squares as calculation of the amount of the  sales forecast. Working capital requirement calculated revenues in 2016. Based on research, analysis and discussion has been said, it can be  concluded that the working capital requirements in 2017 had excess working capital to meet the operational needs of company. Excess working capital may result in idle funds, low income,so the company operations are not efficient in the use of funds channeled to meet the needs of working capital.Keywords : working capital,the velocity of the element of working capital, least square